Neuroprotective Effect of Cinnamaldehyde on Secondary Brain Injury After Traumatic Brain Injury in a Rat Model - YEGEN, BERRAK; AKAKIN, DİLEK; YÜKSEL, MERAL; KOYUNCUOĞLU, TÜRKAN (ELSEVIER SCIENCE INC, 2021)
OBJECTIVE: The aim of this study was to investigate the possible neuroprotective effects of cinnamaldehyde (CA) on secondary brain injury after traumatic brain injury (TBI) in a rat model. METHODS: Rats were randomly divided into 4 groups: control (n = 9), TBI (n = 9), vehicle (0.1% Tween 80; n = 8), and CA (100 mg/kg) (n = 9). TBI was induced by the weight-drop model. In brain tissues, myeloperoxidase ac-tivity and the levels of luminol-enhanced and lucigenin-enhanced chemiluminescence were measured. Inter-leukin 1b, interleukin 6, tumor necrosis factor a, tumor growth factor b, caspase-3, and cleaved caspase-3 were evaluated with an enzyme-linked immunosorbent assay method. Brain injury was histopathologically graded after hematoxylin-eosin staining. Y-maze and novel object recognition tests were performed before TBI and within 24 hours of TBI. RESULTS: Higher myeloperoxidase activity levels in the TBI group (P < 0.001) were suppressed in the CA group (P < 0.05). Luminol-enhanced and lucigenin-enhanced chem-iluminescence, which were increased in the TBI group (P < 0.001, for both), were decreased in the group that received CA treatment (P < 0.001 for both). Compared with the increased histologic damage scores in the cerebral cortex and dentate gyrus of the TBI group (P < 0.001), scores of the CA group were lower (P < 0.001). Decreased number of entries and spontaneous alternation percentage in the Y-maze test of the TBI group (P < 0.05 and P < 0.01, respec-tively) were not evident in the CA group. CONCLUSIONS: CA has shown neuroprotective effects by limiting neutrophil recruitment, suppressing reactive oxygen species and reducing histologic damage and acute hippocampal dysfunction.
Keywords: Antiinflammatory; Antioxidant; Cinnamaldehyde; Neuroprotection; Rat; Traumatic brain injury; ROOT GANGLION NEURONS; NECROSIS-FACTOR-ALPHA; CLOSED-HEAD INJURY; HIGH GLUCOSE; TRANS-CINNAMALDEHYDE; INDUCED DAMAGE; TNF-ALPHA; EXPRESSION; NEUROINFLAMMATION; INTERLEUKIN-1